Isolation of bacterial pathogen Escherichia coli o157:h7 in seafood samples and detection of flich7 gene by using PCR - Marlina Marlina (Indonesian Journal of Pharmacy, 2009)
Escherichia coli O157:H7 is an important human pathogen causing haemorrhagic colitis, haemolytic-uraemic syndrom and thrombotic thrombocytopenic purpura.In this study, P. pelagicus dan P. merguensis samples were collected from markets in Padang from Sept 2007 until Feb 2008. For isolation of the bacteria, samples were firstly enriched in mEC media, followed by plating onto CHROMAgar 0157 for E.coli O157:H7. Consequently, the suspected colonies were confirmed by polymerase chain reaction (PCR) assay using primers specific for O157:H7 to detect a fliCH7 gene. Only 15 of them confirmed as E. coliO157:H7 in PCR assay.Key words: Escherichia coli O157:H7, CHROMAgar 0157, fliCH7 gene, PCR.